Research Priorities in CKD: Report of a National Workshop Conducted in Australia - Tong, Allison; Crowe, Sally; Chando, Shingisai; Cass, Alan; Chadban, Steve J.; Chapman, Jeremy R.; Gallagher, Martin; Hawley, Carmel M.; Hill, Sophie; Howard, Kirsten; Johnson, David W.; Kerr, Peter G.; et al. (American journal of kidney diseases, 2015)
Research aims to improve health outcomes for patients. However, the setting of research priorities is usually performed by clinicians, academics, and funders, with little involvement of patients or caregivers and using processes that lack transparency. A national workshop was convened in Australia to generate and prioritize research questions in chronic kidney disease (CKD) among diverse stakeholder groups. Patients with CKD (n=23), nephrologists/surgeons (n=16), nurses (n=8), caregivers (n=7), and allied health professionals and researchers (n=4) generated and voted on intervention questions across 4 treatment categories: CKD stages 1 to 5 (non–dialysis dependent), peritoneal dialysis, hemodialysis, and kidney transplantation. The 5 highest ranking questions (in descending order) were as follows: How effective are lifestyle programs for preventing deteriorating kidney function in early CKD? What strategies will improve family consent for deceased donor kidney donation, taking different cultural groups into account? What interventions can improve long-term post-transplant outcomes? What are effective interventions for post hemodialysis fatigue? How can we improve and individualize drug therapy to control post-transplant side effects? Priority questions were focused on prevention, lifestyle, quality of life, and long-term impact. These prioritized research questions can inform funding agencies, patient/consumer organizations, policy makers, and researchers in developing a CKD research agenda that is relevant to key stakeholders.